To find the product of the polynomial expressions \((xy + 1)(x - 3)\), we can use the distributive property (also known as the FOIL method for binomials).
-
Distributing \(xy\):
- \(xy \cdot x = x^2y\)
- \(xy \cdot (-3) = -3xy\)
-
Distributing \(1\):
- \(1 \cdot x = x\)
- \(1 \cdot (-3) = -3\)
Now, combining all these terms together:
\[ x^2y - 3xy + x - 3 \]
So the product of the polynomial expressions \((xy + 1)(x - 3)\) is:
\[ x^2y - 3xy + x - 3 \]
Thus, the correct response is:
x²y - 3xy + x - 3.